Photodiodes World Activities in 2011 - Park, Jeong-Woo (IntechOpen, 2011)
Photodiodes or photodetectors are in one boat with our human race. Efforts of people in related fields are contained in this book. This book would be valuable to those who want to obtain knowledge and inspiration in the related area.